Reflexive Hybrid Public Identity: Negotiating Modernity through Capital Conversion among Madurese Santri - Hairus Saleh; Shofiatul Jannah; Shujaur Rahman (Islamika Inside: Jurnal Keislaman dan Humaniora, 2026)
This article examines how expanding social roles reconstruct the public religious identity of Madurese santri. Rather than measuring expansion by the number of occupations, it analyzes the qualitative shift from pesantren-centered piety to participation in education, community organizations, economic initiatives, politics, government, and digital publics. A qualitative single-case study was conducted at Pesantren Mambaul Ulum Bata-Bata in Madura in 2025. Data were generated through in-depth interviews with resident santri, alumni, and ustad, supported by participant observation and institutional documentation. The analysis integrates Bourdieu's concepts of habitus, capital, and field; Giddens' reflexive agency; Hall's identity as positioning; and Bhabha's in-between space. The findings demonstrate four connected movements: the translation of personal piety into public usefulness through khairu al-nasi anfa'uhum li-al-nasi; the conversion of religious knowledge, discipline, networks, and moral reputation into resources recognized in differentiated social fields; reflexive negotiation amid value conflict, competence demands, and public scrutiny; and the formation of an identity that is neither wholly traditional nor uncritically modern. The article conceptualizes this formation as a reflexive hybrid public identity: an institutionally rooted, field-responsive, and service-oriented identity produced through active positioning in public life. It also develops digital religious habitus to explain how pesantren dispositions are reformulated within platform-mediated religious communication.